Peran Hakim Terkait Hak Ex-Officio Dalam Kasus Perceraian Karena Kekerasan Dalam Rumah Tangga (KDRT) Di Pengadilan Negeri Dan Pengadilan Agama Purwokerto - Meliana - Damayanti; Siti - Haniyah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This article aims to determine the ex-officio rights of judges in the case of divorce especially because of domestic violence in Purwokerto religious and District Court regarding the woman rights after divorce. By using mixed-methods within analysis descriptive legal qualitative: a case study and empiric legal method, The findings showed that the judge's decision regarding the rights of women were concluded as follows; 1) the contested or talaq/ divorce cases by verdict judgment could assign or guarantee legally the women rights after divorcing such as Mut'ah, child custody, property rights if not being the charge materials in which judges presumption should not decide the case on the outside of the charge materials (ultra-petition) as long as the judges had legal standing to do so. 2) The judges of Religious and District Court in Purwokerto had the ex officio rights in determining the wife’s rights whether requested or not. The judges were just in case of the cause of divorce where the husband and wife were not willing to be divorced. So, the judges utilized their ex officio rights to punish the husbands for providing Mut'ah according to their ability and feasibility. In brief, the result of this article is the ex officio of the judge is allow to be used to attempt balancing of the parties’ right in divorce cases.